أثر نجاح تطبيق فلسفة الإنتاج في الوقت المحدد كمدخل لتدعيم القدرة التنافسية دراسة ميدانية على الشركات الصناعية الحاصلة على شهادة الأيزو في الساحل السوري - شيخ ديب, صلاح (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر فلسفة الإنتاج في الوقت المحدد (JIT) فلسفة إدارية جديدة، وهي تقوم على أساس استخدام الموارد الصحيحة لإنتاج الكميات المطلوبة في الوقت المناسب والمكان المناسب، خلال وقت إنتاج أقل، وبأقل تكلفة ممكنة، وبأعلى جودة ممكنة، وباستجابة أكبر للعميل، وتخفيض مستويات المخزون، أي أنّ هذه الفلسفة تساعد على تحقيق مركز تنافسي أقوى للمنظمة. وقد توصل الباحث من خلال هذا البحث، واختبار فروض البحث إلى أنّ نجاح تطبيق هذه الفلسفة الجديدة سيؤدي إلى تعظيم القدرات التنافسية، وتحسين جودة المنتج، وتحقيق رضا العميل، وكذلك سيؤدي إلى تخفيض التكلفة في الشركات محل الدراسة. Just in time approach is considered a new managerial philosophy, which depends on using available resources to produce a requested amounts in suitable time and suitable place, in lower production time, reduced production costs, and in high quality, greater customer responsiveness, and lower inventory levels. JIT philosophy can increase the competitiveness position of the firm. The researcher found, after analyzing the results of testing research hypothesis, that the success of applying this new managerial approach, can enhance firm competitiveness position, also this approach can enhance the improvement of the product quality, in addition to enhance the customer satisfaction, in order enhance to reduce the costs in these studied companies.